Linomide prevents the lethal effect of anti-Fas antibody and reduces Fas-mediated ceramide production in mouse hepatocytes. - Redondo, C (1996)
Fas is an apoptosis-signaling receptor molecule expressed in vivo on thymocytes, liver, heart, and ovary. In vivo administration of the anti-Fas Jo2 antibody in mice induces severe apoptotic liver damage leading to fulminant hepatitis and death. Linomide, a quinoline 3-carboxamide, inhibits apoptosis of B and T cells induced by various stimuli including viruses, superantigens, and glucocorticoids. Mice treated with linomide survived the lethal effect of anti-Fas antibody, did not accumulate ceramide in hepatocytes, and recovered liver structure and function within 96 h of anti-Fas injection, as confirmed by histology and glutamic oxalacetic transaminase, glutamic pyruvic transaminase, and lactate dehydrogenase levels. Surviving mice showed severe depletion of cortical thymocytes, but medullar thymic cells expressing high CD3 and Fas levels also survived the treatment with anti-Fas in the presence of linomide. Heart, lung, and ovary showed no signs of apoptosis promoted by Fas ligation. These results suggest that linomide prevents cell death triggered by Fas ligation and can be useful for therapeutic intervention in fulminant hepatitis.